P-259 What's in a name...?. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Heggie, Jon; Stone, Jackie
Abstract : Background: A brand is only as important and meaningful as the people who live and breathe it, and the values that underpin it. In a hospice in Scotland we wanted to know what does our brand really mean to the families, volunteers, staff and supporters invested in our work? As a part of development of our strategy we took a critical review of our brand including language, tone of voice and imagery. Methodology: The following critical questions underpinned our work: Are we expressing who we are with honesty, integrity and purpose?; Does our brand truly reflect who we are, and what we aspire to be in terms of care and support right across our community; Does our name reflect care delivered not only in a building but also in homes and community settings across our area? Working with a local, personal, and inspiring marketing agency we conducted a mixed methodology review including staff, volunteers and supporters. This took place through workshops, 1:1 interviews and anonymous comments cards around the hospice and shops. Each of these interaction opportunities not only looked at our brand but tied in important questions that would feed into our evolving strategy, mission and vision work. Results: The information, ideas and thoughts gathered have been collated into ideas around what our brand proposition could look like going forward. What makes us special, what sums up who we are, and what makes us unique and inspiring has been turned into working ideas that are being shared widely across our stakeholders. This is an iterative process that will grow and develop as feedback is gathered. Next Steps: The results will be delivered in the summer of 2019.